Preston lee's conversation english for ukrainian speakers lesson 1 ebook 40. - Lee, Preston (Smashwords Edition, 2020)
This book is designed to help English learners begin speaking conversation English. It is also an excellent learning resource for reading and comprehension. Have fun and learn English the easy way. This book has been written for all ages, children and adults alike. - Written for all ages - 40 excellent lessons for everyday English conversation - 40 fun worksheets for review - Practice tests to reinforce learning - Activity pages for easy learning - Frequently used verbs in 4 grammatical forms - 40 practical and commonly used idioms - Vocabulary words include Ukrainian translations Written by ESL specialists, Kevin Lee and Matthew Preston have taught English as a Second Language for over 20 years around the world. The lessons in this book have been carefully chosen to help the learner really understand a range of topics for everyday talk. A great book to be used with Preston Lee's Beginner English 100 Lessons